Traditional and Web-Based Technologies to Improve Partner Notification Following Syphilis Diagnosis Among Men Who Have Sex With Men in Lima, Peru: Pilot Randomized Controlled Trial - Clark, Jesse L (2018)
Background: Patient-initiated partner notification (PN) following the diagnosis of a sexually transmitted infection is a critical component of disease control in men who have sex with men (MSM) sexual networks. Both printed and internet-based technologies offer potential tools to enhance traditional partner notification approaches among MSM in resource-limited settings. Objective: This randomized controlled trial aimed to evaluate the effect of 2 different PN technologies on notification outcomes following syphilis diagnosis among MSM in Peru: A Web-based notification system and patient-delivered partner referral cards. Methods: During 2012-2014, we screened 1625 MSM from Lima, Peru, for syphilis infection and enrolled 370 MSM with symptomatic primary or secondary syphilis (n=58) or asymptomatic latent syphilis diagnosed by serology (rapid plasma reagin, RPR, and Microhemagglutination assay for Treponema pallidum antibody; n=312). Prior to enrollment, potential participants used a computer-based self-interviewing system to enumerate their recent sexual partnerships and provide details of their 3 most recent partners. Eligible participants were randomly assigned to one of 4 intervention arms: (1) counseling and patient-initiated Web-based PN (n=95), (2) counseling with Web-based partner notification and partner referral cards (n=84), (3) counseling and partner referral cards (n=97), and (4) simple partner notification counseling (control; n=94). Self-reported partner notification was assessed after 14 days among 354 participants who returned for the follow-up assessment. Results: The median age of enrolled participants was 27 (interquartile range, IQR 23-34) years, with a median of 2 partners (IQR 1-5) reported in the past month. Compared with those who received only counseling (arm 4), MSM provided with access to Web-based partner notification (arms 1 and 2) or printed partner referral cards (arms 2 and 3) were more likely to have notified one or more of their sexual partners (odds ratio, OR, 2.18, 95% CI 1.30-3.66; P=.003 and OR 1.68, 95% CI 1.01-2.79; P=.045, respectively). The proportion of partners notified was also higher in both Web-based partner notification (241/421, 57.2%; P<.001) and referral card (240/467, 51.4%; P=.006) arms than in the control arm (82/232, 35.3%). Conclusions: Both new Web-based technologies and traditional printed materials support patient-directed notification and improve self-reported outcomes among MSM with syphilis. Additional research is needed to refine the use of these partner notification tools in specific partnership contexts.